El debate andaluz / [director de la ed., Francisco Rubiales Moreno] - Rubiales Moreno, Francisco
Contiene textos de Alejandro Rojas-Marcos, Carlos Sanjuan, Manuel Chaves, Pedro Aparicio, Cándido Méndez, Herminio Trigo, José Rodríguez de la Borbolla, Pedro Solbes, Manuel Pezzi, Cristina Almeida, Francisco Vallejo Serrano, Juio Anguita, José Bono, Gaspar Zarrías Arévalo, Magdalena Álvarez, Antonio Gutiérrez